Realizacja wzorca listu elektronicznego na przykładzie relacji student — uczelnia - Tarary, Eliza (Poznańskie Spotkania Językoznawcze, 2014)
The article tries to characterize one of the Internet genres – an electronic letter. More than 400 letters addressed by students to university have been studied. The relationship studentuniversity is the materialization of the relationship petitioner-office. The construction of the studied e-mails is typical of the generic pattern being formed. An electronic letter is basically composed of a letterhead and the ending, between which the proper contents of a letter are inserted. A part of the analyzed correspondence demonstrates features typical of an application – a genre of the official style. In their e-mails addressed to different institutions, students made numerous language mistakes, including syntactical, lexical and orthographic/punctuation mistakes.